Modelo de negocio de una plataforma para el cuidado de mascotas - Guardia Quiroz, Marco Antonio (2020)
|n the last 10 years having a pet have changed from just kept and feed it to be part of our family as a member. This change in the mind-set of the society develop a paternal bond with them which lead us to go from being just a “pet owner” to become a “pet parent”. In the same way that the adoption and consideration of pets as life companions evolves, the pet care services are increasing in terms of alternatives and sophistication, for example now we have spa for pets, birthday parties, walkers, crematoriums, among others. For pet parents, this means spending more time searching for information in every source available. And on the market side (veterinary mainly), it opens the opportunity for better and new alternatives to offer. To archive this connection between them, we present WAYKI a digital platform that centralizes information of pet care services, allowing it to be managed in a friendly and simple way, ensuring the well-being of the pet and the tranquility of the Pet's Parent. As a result of this thesis, we identify a high probability acceptance for using a tool that facilitates the search and hiring of pet care health services, from both sides. Likewise, a big interest is identified in the use of a tool that facilitates the administration of the pet's medical history